STATINS AND RISK OF INFECTIOUS DISEASES - O. M. Drapkina; R. N. Shepel' (Столичная издательская компания, 2015)
Besides hypolipidemic effect statins demonstrate some not-lipid (pleotropic) ones. Special attention has been paying to statin inducing reduction in bacterial infections incidence and severity, and pneumonia particularly. Results of the large studies on statin influence on infectious disease are presented.